Peran Penyuluhan Keluarga Berencana dalam Meningkatkan Pengetahuan KB pada Pasangan Usia Subur (PUS) Kelompok Masyarakat Miskin - Anna Fatchiya; Asri Sulistyawati; Budi Setiawan; Rizal Damanik (Jurnal Penyuluhan, 2021)
Family planning (KB) is an effective effort to control the population and at the same time improve a better life for the community, especially for poor families. The availability of information and extension services is important to increase the participation of fertile aged couples (PUS) in poor families in accessing family planning services. For this reason, this study aims to (1) describe the level of knowledge of PUS poor families on family planning information and counseling, and (2) to analyze the effect of extension agents on the level of knowledge of PUS about family planning. Data were collected through a survey method using questionnaire on 120 respondents representing PUS in poor families in Bogor Regency and Bogor City. Each district / city was selected the sub-district that had the highest number of poor PUS. The results showed that the level of knowledge about family planning with the poor in PUS was classified as low. The results of statistical tests show that extension services have an effect on the level of knowledge of the PUS about family planning.